2002
DOI: 10.1207/s15327078in0304_07
|View full text |Cite
|
Sign up to set email alerts
|

Infants' Responses to Gender‐Inconsistent Events

Abstract: Toddlers' knowledge of the stereotyping of traditionally feminine and masculine household activities was examined using the preferential looking paradigm. Seventy‐seven 24‐month‐old infants observed a series of 9 pairs of photographs, each portraying a male and female adult engaged in the same stereotyped or gender‐neutral activity (e.g., ironing, hammering, or reading). Longer looking times were predicted on stimuli inconsistent with gender stereotypes (e.g., looking longer at the man putting on lipstick than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 15 publications
3
32
0
3
Order By: Relevance
“…However, mothers of girls engaged in "other interaction" significantly more than did mothers of boys, usually in the form of the mothers comforting and hugging their daughters. These different behaviors further contribute to the gender norms and expectations that boys are supposed to be independent and strong, whereas girls are supposed to display emotion and be dependent upon other people (Serbin, Poulin-Dubois, & Eichstedt, 2002). Girls were reinforced with comfort and a sense of security for engaging with their mothers, and boys were not.…”
Section: Discussionmentioning
confidence: 98%
“…However, mothers of girls engaged in "other interaction" significantly more than did mothers of boys, usually in the form of the mothers comforting and hugging their daughters. These different behaviors further contribute to the gender norms and expectations that boys are supposed to be independent and strong, whereas girls are supposed to display emotion and be dependent upon other people (Serbin, Poulin-Dubois, & Eichstedt, 2002). Girls were reinforced with comfort and a sense of security for engaging with their mothers, and boys were not.…”
Section: Discussionmentioning
confidence: 98%
“…First, during the toddler and preschool years, children begin learning about gender-related characteristics. Empirical studies have found that children develop the awareness for gender role appropriateness as early as their second birthday (e.g., Serbin et al 2002). In the second phase, 4-to 5-year-olds are rapidly learning to distinguish, value, and internalize the gender cues for maleness and femaleness.…”
Section: Learning Gender Stereotypesmentioning
confidence: 99%
“…Gender stereotypes and their use in the understanding of the social world can be observed in the study of toys due to precocity of gender preference in the developmental age. It seems that children, at 18 months of age, choose stereotypical toys according to gender (e.g., Powlishta, Sen, Serbin, Poulin-Dubois, & Eichstedt, 2001;Serbin, Poulin-Dubois, Colburne, Sen, & Eichstedt, 2001) and, by 2 years old, acquire some knowledge of the gender stereotyping of masculine and feminine activities and prefer to play with toys judged to pertain to their own sex rather than with neutral toys or stereotypical toys for the opposite sex (e.g., Martin, Eisenbud, & Rose, 1995;Leinbach, Hort, & Fagot, 1997;Serbin, Poulin-Dubois, & Eichstedt, 2002). Children, between 3 and 6 years old, appear to have better memories for information consistent with gender-type than for information inconsistent with gender-type (Liben & Bigler, 2002), and also for toys and activities labeled or stereotyped for their own, relative to the opposite sex (Cherney & London, 2003;Cherney, 2005).…”
mentioning
confidence: 99%